Quantitative Sensory Testing Across Chronic Pain Conditions and Use in Special Populations - Weaver, Kristen R.; Griffioen, Mari A.; Klinedinst, N. Jennifer; Galik, Elizabeth; Duarte, Ana C.; Colloca, Luana; Resnick, Barbara; Dorsey, Susan G.; Renn, Cynthia L. (Frontiers in Pain Research, 2022)
Chronic pain imposes a significant burden to the healthcare system and adversely affects patients' quality of life. Traditional subjective assessments, however, do not adequately capture the complex phenomenon of pain, which is influenced by a multitude of factors including environmental, developmental, genetic, and psychological. Quantitative sensory testing (QST), established as a protocol to examine thermal and mechanical sensory function, offers insight on potential mechanisms contributing to an individual's experience of pain, by assessing their perceived response to standardized delivery of stimuli. Although the use of QST as a research methodology has been described in the literature in reference to specific pain populations, this manuscript details application of QST across a variety of chronic pain conditions. Specific conditions include lower extremity chronic pain, knee osteoarthritis, chronic low back pain, temporomandibular joint disorder, and irritable bowel syndrome. Furthermore, we describe the use of QST in placebo/nocebo research, and discuss the use of QST in vulnerable populations such as those with dementia. We illustrate how the evaluation of peripheral sensory nerve function holds clinical promise in targeting interventions, and how using QST can enhance patient education regarding prognostic outcomes with particular treatments. Incorporation of QST methodology in research investigations may facilitate the identification of common mechanisms underlying chronic pain conditions, guide the development of non-pharmacological behavioral interventions to reduce pain and pain-related morbidity, and enhance our efforts toward reducing the burden of chronic pain.